Passive Energy Recovery Snubber Based DC-DC Boost Converter - Radika, P. (Asian Journal of Electrical Sciences, 2014)
A dc-dc boost converter capable of delivering a high output voltage and efficiency is proposed. The proposed converter uses passive energy recovery snubber. The snubber is used to reduce the turn-off loss of the main switch and the snubber stored energy is effectively recovered into the output side. The simulation and experimental results of the proposed converter is compared with a conventional boost converter at low voltage conditions. The results obtained shows that the proposed model has high output voltage, efficiency and low switching loss.